Literasi Kesehatan dalam Meningkatkan Peran Keluarga sebagai PMO dan Kepatuhan Pengobatan TBC - Jalilah Azizah Lubis; Elda Sari Siregar; Khatib Lubis; Meliani Sari Siahaan; Ika Handayani Siregar; Aldi Syaputra Nasution (Linguistik : Jurnal Bahasa dan Sastra, 2026)
This study aims to analyze the level of public understanding of TB and its relationship to family roles, treatment adherence, and socioeconomic support. The method used in this study was a quantitative descriptive design with a survey approach. Data were collected from 40 respondents through a questionnaire consisting of 25 indicators divided into four domains: knowledge about TB (5 indicators), the role of the family as a PMO (6 indicators), treatment adherence (5 indicators), and socioeconomic support (9 indicators). Data analysis was performed by calculating the total score per domain and the percentage of achievement. The results showed that the level of knowledge about TB was in the high category with an average achievement above 80%. The role of the family as a PMO showed a variation in achievement between 77.5% and 95%. Treatment adherence had the lowest achievement in several indicators (40–60%), while socioeconomic support showed a fairly wide variation between 27.5% and 87.5%. Public health literacy about TB is generally good, but there are challenges in aspects of treatment adherence and several components of socioeconomic support. Interventions involving strengthening the role of the family and increasing socioeconomic support are needed to improve the success of TB treatment.